Changes in circulating microRNAs levels with exercise modality - Banzet, Sébastien; Chennaoui, Mounir; Girard, Olivier; Racinais, Sébastien; Drogou, Catherine; Chalabi, Hakim; Koulmann, Nathalie (Journal of applied physiology (1985), 2013)
Here, we studied muscle-specific and muscle-related miRNAs in plasma of exercising humans. Our aim was to determine whether they are affected by eccentric and/or concentric exercise modes and could be biomarkers of muscle injuries or possible signaling molecules. On two separate days, nine healthy subjects randomly performed two 30-min walking exercises, one downhill (high eccentric component) and one uphill (high concentric component). Perceived exertion and heart rate were higher during the uphill exercise, while subjective pain and ankle plantar flexor strength losses within the first 48-h were higher following the downhill exercise. Both exercises increased serum creatine kinase and myoglobin with no significant differences between conditions. Plasma levels of circulating miRNAs assessed before, immediately after, and at 2-, 6-, 24-, 48-, and 72-h recovery showed that 1) hsa-mir-1, 133a, 133b, and 208b were not affected by concentric exercise but significantly increased during early recovery of eccentric exercise (2 to 6 h); 2) hsa-mir-181b and 214 significantly and transiently increased immediately after the uphill, but not downhill, exercise. The muscle-specific hsa-mir-206 was not reliably quantified and cardiac-specific hsa-mir-208a remained undetectable. In conclusion, changes in circulating miRNAs were dependent on the exercise mode. Circulating muscle-specific miRNAs primarily responded to a downhill exercise (high eccentric component) and could potentially be alternative biomarkers of muscle damage. Two muscle-related miRNAs primarily responded to an uphill exercise (high exercise intensity), suggesting they could be markers or mediators of physiological adaptations.